Behavioral Counseling with Engineering Modeling and Technique Token Economy to improve Confidence - Sari, Km. Shintia Agustini Purnama; N. Dantes, N. Dantes; Arum MWP, Dewi (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This study aims to determine the effect of behavioral counseling with modeling techniques and token economy techniques to improve self-confidence in learning in students of class X SMA N 1 Singaraja. This research type is quasi experiment with research design noequivalent pretest-posttest control group design. In this study using purposive sampling technique. Testing Hypothesis 1, found t count = 11.37. The results should be consulted with t table. Based on dk = n-1 = 12-1 = 11 at the level of significance 0.05 obtained t table = 2.201. This means t arithmetic 11.37> t table 2.201. Testing Hypothesis 2 found t arithmetic = 11.48. The results should be consulted with t table. Based on dk = n-1 = 12-1 = 11 at the level of significance 0.05 obtained t table = 2.201. This means t arithmetic 11.48> t table 2.201. Result Hypothesis 3 get coefficient of F count equal to 13,588> with db: 1; 10 = 4,96. If set significance level α = 0.05.